The Position of Heirs Who Re-Converted to Islam After the Heir Died - Arifin, Muhammad (Inspiring Law Journal, 2022)
According to Islamic law there are people who are entitled to receive inherited property under certain conditions, but there are also people who actually have the right to receive inheritance, but are hindered from obtaining inherited property due to certain factors as well. One of the factors that prevents a person from obtaining inheritance is the religious difference between the heir and the heir. It becomes a problem when there are heirs of different religions who demand to get inherited property because they have converted to Islam again and consider themselves still entitled to inherited property. Based on the results of the study, it was found that the position of heirs who converted to Islam returned after the sipewaris died and before the division of inheritance, still did not get inherited property. This is because what is a hindrance is that religious differences are taken into account when the heir dies, because the division of inheritance begins when the heir dies.